Ectopic neurons and aberrant connections during neural development. - Clarke, P G (1975)
During the normal development of the nucleus of origin of centrifugal fibers to the chick retina (the so-called isthmo-optic nucleus) a significant number of neurons are misrouted during their migration from the neural epithelium in which they are generated. Like the cells in the isthmo-optic nucleus, these ectopic neurons can be identified by the retrograde transport of horseradish peroxidase (donor: hydrogen peroxide oxidoreductase, EC 1.11.1.7) injected into the eye. Between 500 and 600 such cells have been identified on one side of the brain of 12 to 15-day-old embryos, but only about 10% of this number is seen beyond hatching. In addition, during development some of the cells in the nucleus send their axons to the ipsilateral retina, whereas in post-hatched animals they all project to the contralateral retina. The number of such neurons with aberrant axons is greatly increased (in some cases by as much as two orders of magnitude) in chicks from which one eye was removed early in development. Although normally about 60% of the neurons in the isthmo-optic nucleus degenerate between the 13th and 17th days of incubation, they can almost all be labeled by intraocular injections of horseradish peroxidase on the 12th day, indicating that the axons of virtually all the cells, including those neurone that subsequently die, reach the retina.